Henry VIII (Res Medica, 2013)
From a Dissertation to the Royal Medical Society by G. DevonaldThis short article could have been aptly subtitled Sex, Syphilis and Sores, because this accurately conveys the impression that most people have of Henry VIII.  Mention his name, and a lecherous look comes into a person’s eye and he immediately makes some remark about Henry’s six wives and his syphilis. So much good and so much evil has been written about him that he must be the most controversial king in British history. Dickens described him as “a blot of blood and grease”, yet others have thought him to be the paragon of all the virtues. Religious convictions obviously played their part in colouring the opinions of earlier writers, Henry being Bluff King Hal, the merry, innocent monarch to the Protestant, and a cruel, sadistic ogre to the Catholic. The truth is that both sides were partly right. When Henry came to the throne he was considered to be the most intelligent, most tolerant and most athletic of all European kings. He was kind, considerate and reasonable, even Erasmus thought that his crowning heralded a Golden Age in the English Renaissance. Yet during his early forties a change came over him and he became an irritable, selfish, suspicious tyrant. At that time Castilian, the French ambassador described him as “the most dangerous and cruel man in the world”.